Interrelation between oxygen non-stoichiometry and Fe/Mo superstructural ordering in Sr2FeMoO6-d - L. I. Hurski; N. A. Kalanda; M. V. Yarmolich; V. A. Turchenko; D. V. Karpinsky; V. A. Chumak; A. V. Petrov; A. L. Zhaludkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Single-phase Sr2FeMoO6-d powders with various degrees of superstructural ordering of Fe/Mo cations and oxygen index d were obtained by solid-phase synthesis. With the help of X-ray phase analysis and neutron diffraction studies it has been established that the Fe-O1 and Mo-O2 values decrease with increasing oxygen content and the superstructural ordering of Fe/Mo cations increases, whereas the Fe-O2 and Mo-O1 bond lengths decrease, which leads to a decrease in the crystal lattice parameters and in the unit cell volume accordingly. This indicates an increase in the covalence of the bond along the axis (c), which stimulates the redistribution of the electron density from the (Fe/Mo-O2) layers to the (Fe/Mo-O1) layers and to an increase in the concentration of spin-polarized electrons with spins¯, which are located in the conduction band on Mo(t2g)¯ electron orbitals. When studying the dynamics of the change in oxygen non-stoichiometry and the degree of superstructural ordering it was found that the rate of desorption of oxygen is several times larger than the rate of Fe/Mo cations ordering.